2006
DOI: 10.1074/jbc.m513686200
|View full text |Cite
|
Sign up to set email alerts
|

An Interaction between Insulin-like Growth Factor-binding Protein 2 (IGFBP2) and Integrin α5 Is Essential for IGFBP2-induced Cell Mobility

Abstract: In the study we report here, we tested the hypothesis that insulinlike growth factor-binding protein 2 (IGFBP2) promotes cell mobility through its interaction with integrin ␣5. Our previous microarray studies showed that IGFBP2 activates the expression of integrin ␣5. In addition, IGFBP2 has an Arg-Gly-Asp (RGD) domain, which is a known integrin binding motif. We first confirmed our microarray results by showing that the expression of integrin ␣5 is indeed up-regulated at the protein level in IGFBP2-overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 24 publications
(24 reference statements)
4
97
0
Order By: Relevance
“…In addition, we observed that IGFBP2 alone has no effect on astrocytoma cell growth in vitro, whereas it positively affects astrocytoma cell motility. Both results are in agreement with previous studies recently published in literature (Levitt et al, 2005;Wang et al, 2003Wang et al, , 2006. The latter of these studies reported that IGFBP2 promotes astrocytoma cell motility through interaction between the integrin a5 subunit and its RGD domain.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, we observed that IGFBP2 alone has no effect on astrocytoma cell growth in vitro, whereas it positively affects astrocytoma cell motility. Both results are in agreement with previous studies recently published in literature (Levitt et al, 2005;Wang et al, 2003Wang et al, , 2006. The latter of these studies reported that IGFBP2 promotes astrocytoma cell motility through interaction between the integrin a5 subunit and its RGD domain.…”
Section: Discussionsupporting
confidence: 93%
“…The data are expressed in terms of means 6 SE normalized so that the control (CT) mean was set to 100. As compared with CT, only the significant differences (posthoc tests) are indicated as *P < 0.05, **P < 0.01, and ***P < 0.001. the IGFBP2-IGFII complex may also prevent the interaction between the IGFBP2 RGD domain and the integrin a5 subunit, showed by Wang et al (2006) as being essential for the IGFBP2-induced cell motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data support this hypothesis, in that IGFBP2 was shown to independently promote cell mobility through its interaction with integrins (Schütt et al, 2004;Wang et al, 2006). Moreover, IGFBP2 has been described to be a candidate biomarker for PTEN status and PI3K/Akt pathway activation (Mehrian-Shai et al, 2007).…”
Section: Discussionmentioning
confidence: 51%
“…While IGFBP2 exhibits IGF-dependent inhibitory effects on growth of many types of cells [137], it also displays IGF-independent activities [69,70,[138][139][140][141][142][143][144][145][146]. We identified IGFBP2 from a cancerous cell line as a supportive secreted factor for mouse and human HSCs [69,147].…”
Section: Igf Binding Proteinmentioning
confidence: 99%